Preparation and Properties of Hydrophobically Modified Whey Protein Isolate-Pullulan Composite Aerogel - Qinglong CAO; Hao WU; Wenjing GAO; Qiao LEI (Shipin gongye ke-ji, 2022)
Objective: To modify hydrophobicity of protein/polysaccharide aerogels and evaluate their properties. Methods: The whey protein isolate(WPI)- pullulan(PUL) composite aerogels were treated by low temperature plasma treatment. After exposure to hydroxyl groups, silane coupling agents were used for surface grafting. Hydrophobic composite aerogels were obtained, and their hygroscopicity, hydrophobicity, oil content, compression resistance, thermal weightlessness, loading and slow release properties of essential oils were studied. Results: The equilibrium moisture absorption rate of the composite aerogel modified by methyltrimethoxy silane(methyltrimethoxysilane, MTMS) was (9.67%±0.323%), eighteen alkyl trimethoxy silane(octadecyltrimethoxysilane, OTMS) modified composite aerogel equilibrium moisture absorption rate of (9.34%±0.276%), compared with before modification(11.41%±0.506%). It was significantly reduced; Before modification, the contact angle of composite gas gel was (40.14°±2.16°), the oil contact angle was (28.07°±2.43°); The contact angle of water after MTMS modification was (82.10°±4.78°), the oil contact angle was (56.14°±3.25°); The contact angle of water after OTMS modification was (85.21°±4.61°), the oil contact angle was (74.63°±3.08°); The hydrophobic and oil drainage properties of the modified products were improved, and the effect of OTMS was better. Compression modulus of modified composite aerogel(21.745±1.982) MPa, (17.655±3.034) MPa after MTMS modification, (18.412±3.513) MPa after OTMS modification. The compressive strength of the modified material decreased slightly, but it did not affect the normal use. The maximum loading rate of the modified composite aerogel clove essential oil was (254.26%±5.585%), after MTMS hydrophobic modification, the maximum loading rate of clove essential oil was (241.57%±5.214%) and OTMS group (223.31%±4.436%). The loading rate of clove essential oil had decreased, but the sustained release property had been improved, and the MTMS modified slow-release effect was better. The thermal stability of OTMS group was better. Conclusion: Silane graft hydrophobic modification can significantly enhance the hydrophobicity and enhance the hydrophobicity of composite aerogels. It is suitable for loading and slow releasing applications of active oils, which widens the application field of WPI-PUL composite aerogels.